SAFETY, QUALITY CONTROL, AND SUSTAINABILITY IN CONSTRUCTION: EXPLORING THE NEXUS - A REVIEW - Joy Otibhor Olurin; Joachim Osheyor Gidiagba; Vincent Ebhohime Ehiaguina; Tina Chinyere Ndiwe; Gabriel Gbenga Ojo; Oluwaseun Ayo Ogunjobi (Engineering Heritage Journal)
This comprehensive review elucidates the intertwined relationship between safety, quality control, and sustainability within the construction sector, highlighting the critical need for integrating these elements to promote optimal project outcomes and long-term industry advancement. The study commences with an in-depth exploration of existing literature, focusing on diverse methodologies, strategies, and frameworks employed to enhance safety and enforce stringent quality control, thus contributing to the overall sustainability of construction projects. Safety is identified as a paramount concern in construction, significantly influencing both quality and sustainability. The lack of safety not only jeopardizes human lives but also results in cost overruns and project delays, undermining the overall quality and sustainability. Quality control, herein, is discussed in relation to its pivotal role in minimizing errors and rework, ensuring adherence to standards, and facilitating the attainment of sustainability goals through resource efficiency and waste reduction. Sustainability in construction is dissected through its three foundational pillars: economic viability, social equity, and environmental integrity. This review details how the integration of safety and quality control significantly impacts these pillars, highlighting the synergy between construction practices, resource optimization, stakeholder well-being, and ecological preservation. Empirical studies, theoretical frameworks, and case studies form the basis of this review, providing a multifaceted understanding of the interdependence between safety, quality control, and sustainability in construction. The assessment reveals that the construction industry is progressively acknowledging the inherent connection between these components, with contemporary practices and policies increasingly reflecting an integrated approach. The article concludes by underscoring the imperative for continuous research and development, innovations, and policy interventions to strengthen the nexus between safety, quality control, and sustainability in construction. It also advocates for a holistic approach that unifies these elements to drive industry resilience, promote sustainable development, and ensure the well-being and prosperity of communities and the environment.